Use of ox-drawn scoops for pond maintenance in the southern Ethiopian rangelands - Haile-Selassie, A.; Cossins, N.J. (International Livestock Centre for Africa, 1985)
Reports the initial results of a trial conducted to study the feasibility of using ox-drawn scoops for desilting ponds in the Ethiopian highlands.